Menopausal hormone therapy and central nervous system tumor risk: Large UK prospective study and meta-analysis. - Benson, V; Kirichek, O; Beral, V; Green, J (2014)
Female sex hormones are thought to affect women's risk of developing central nervous system (CNS) tumors. Some have reported an increased risk in users of menopausal hormone therapy (HT) but evidence is limited. In the UK General Practice Research Database we compared prospectively collected information on HT prescriptions in women aged 50-79 years with CNS tumors diagnosed in 1987-2011 with that in matched controls (four per case). Relative risks (RRs) in relation to prescribed HT were calculated overall and by CNS tumor subtype. Statistical tests are two-sided. For all CNS tumors (n = 3,500), glioma (n = 689), meningioma (n = 1,197), acoustic neuroma (n = 439), and pituitary tumors (n = 273) adjusted RRs for women prescribed HT versus not were, respectively, 1.21 (95% confidence intervals (CI) = 1.10-1.32, p < 0.0001), 1.14 (0.93-1.40, p = 0.2), 1.30 (1.11-1.51, p = 0.001), 1.37 (1.06-1.75, p = 0.01), and 1.35 (0.99-1.85, p = 0.06). There was no significant difference in risk by tumor subtype (pheterogeneity  = 0.6). A meta-analysis was conducted, combining our results with those from other published studies with prospectively collected exposure information. The meta-analyses yielded significantly increased risks for all CNS tumors, glioma and meningioma in users of estrogen-only [1.35 (1.22-1.49), 1.23 (1.06-1.42) and 1.31 (1.20-1.43), respectively] but not estrogen-progestin HT [1.09 (0.99-1.19), 0.92 (0.78-1.08) and 1.05 (0.95-1.16), respectively]; these differences were statistically significant (p < 0.005 for each tumor type). There was no significant difference between glioma and meningioma risk in users of estrogen-only HT. The totality of the available evidence suggests an increased risk of all CNS tumors (and of glioma and meningioma separately) in users of estrogen-only HT. Absolute excess risk (2 per 10,000 users over 5 years) is small.